Polyethylene glycol (PEG-400) mediated synthesis of quinoxalines - Nagarapu, Lingaiah; Mallepalli, Raghu; Arava, Glory; Yeramanchi, Lingappa (European Journal of Chemistry, 2010)
A simple and highly efficient protocol for the synthesis of quinoxaline derivatives from various ortho-phenylenediamines with α-halo ketones under catalyst free conditions is reported by using polyethylene glycol (PEG-400) as an efficient recyclable medium without using any organic co-solvent or additive. This protocol gives wide range of quinoxaline derivatives with high yields.